Effect of carbonation sources and its addition levels on carbonated mango juice - Thongrote C. (2017)
© All Rights Reserved. The present study was aimed to investigate the effect of carbonation sources (carbonated water or dry ice) and its supplementation levels on the physiochemical, microbial and sensorial qualities of carbonated mango juice. Experimental results revealed that the overall qualities of carbonated mango juice, especially sensory properties, obtained from the addition of dry ice were higher than those of carbonated water. Higher levels of carbonated water significantly decreased total acidity and ascorbic acid content of the carbonated mango juice (p < 0.05). On the other hand, different levels of dry ice addition did not significantly affect the physicochemical properties of the carbonated mango juice (p > 0.05). All of the carbonated mango juice samples had a low microbial number, which was not affected by the carbonation method and levels of the carbonation source.